Economic, Legal and Cultural Determinants of Changes in Employment of People with Disabilities : Perspective Employers and the Challenges for Social Policy - Giermanowska, Ewa (Studia Oeconomica Posnaniensia, 2015)
The Polish model of vocational rehabilitation and employment is of low efficiency in respect of employment employment and requires change. Activity of those with disabilities is at a very low level. A key party to the employment relationship are the employers whose attitudes and commitment are highly influential in providing jobs for people with disabilities. The article covers the changes in the system to support the employment of people with disabilities, taking into account the perspective of employers and a change in the society. Economic instruments have a limited impact on the employment of workers with disabilities in the open labour market. The prejudices and stereotypes that are to be found amongst employers and employees are the biggest barriers to the employment of people with disabilities. Studies of good practice in organizations employing persons with disabilities indicate that culture plays an important role. The values , norms and beliefs shared by employers and employees, as reflected in its organizational culture and management of different categories of employees are of great significance.